AN INTEGRATIVE APPROACH BETWEEN WASTE MATERIAL TECHNOLOGY AND ENVIRONMENTAL IMPACT MITIGATION STRATEGIES - Kusnadi Jarek (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2025)
Environmental problems due to increased waste demand innovative and sustainable solutions. This study aims to examine an integrative approach between waste material technology and environmental impact mitigation strategies. The method used is descriptive qualitative with a case study approach, through field observations, in-depth interviews, and documentation studies. The results of the study show that the use of waste treatment technology, such as making paving blocks from recycled plastics and fly ash-based geopolymers, is able to significantly reduce the volume of waste and produce products with high use value. Environmental mitigation strategies, such as policy incentives and educational campaigns, have been proven to strengthen the implementation of these technologies. The success of integration is also influenced by multi-stakeholder collaboration involving society, academia, government, and the private sector. This approach not only offers technical solutions, but also creates a sustainable socio-ecological system. Therefore, the integration between waste technology and mitigation strategies needs to be continuously developed as part of efforts to realize sustainable development based on resource efficiency, environmental protection, and community empowerment.